Fiji : Staff Report for the 2002 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2003)
This 2002 Article IV Consultation highlights that following the political crisis, Fiji experienced sharp declines in tourism earnings, while external sanctions adversely affected investment and textile exports. As a result, GDP fell 2 3/4 percent in 2000, and the current account deficit widened to 6 1\2 percent of GDP. Financial stability and the basket peg of the Fiji dollar were maintained through tightening of domestic monetary policy and exchange controls, together with government spending cuts to offset the impact of weaker growth on the fiscal deficit.